Acral erythema with bullous formation: a side effect of chemotherapy in a child with acute lymphoblastic leukemia - Aytaç, Selin; Gümrük, Fatma; Cetin, Mualla; Tuncer, Murat; Yetgin, Sevgi (The Turkish Journal of Pediatrics, 2010)
Chemotherapy-induced acral erythema (CIAE) with bullous formation is an uncommon complication in children. We describe herein a child who developed CIAE with bullous formation following high-dose methotrexate and cytarabine for relapsed acute lymphoblastic leukemia. The rash completely resolved within two weeks of the appearance without any specific treatment. CIAE may develop in children with hematological malignancies as a complication of pediatric chemotherapeutic regimens, and pediatricians should be aware of this phenomenon despite its rarity.